The Plum in the Golden Vase or, Chin P'ing Mei, Volume Five : The Dissolution - Xiaoxiaosheng (Book collections on Project MUSE., 2013)
Volume five translation of the classic sixteenth-century Chinese novel on the domestic life of a corrupt merchant.